2011
DOI: 10.1116/1.3525280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precursor chemistry and growth temperature on the electrical properties of SrTiO3-based metal-insulator-metal capacitors grown by atomic layer deposition

Abstract: SrTiO 3 thin films were grown to thicknesses in the range of 18–30 nm by atomic layer deposition using Sr(Pir3Cp)2 and (CpMe5)Ti(OMe)3 as strontium and titanium precursors at 250 and 300 °C. Water or ozone was used as oxygen precursor. The films were amorphous in as-deposited state, but crystallized as cubic SrTiO3 after annealing at 650 °C. The highest permittivity values, 60–65, were achieved in the films deposited with ozone at 300 °C. The films grown at 250 °C tended to possess markedly lower leakage curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the case of an as-deposited sample, the y-axis intercept is negative: the adjustment is not good (we have only three points available), the error covers the origin, so no conclusions can be obtained in this case. In a previous work with SrTiO 3based films (STO) we found different k-values for different film thicknesses as the crystallization intensities of these films were low for thinner films [19].…”
Section: Resultsmentioning
confidence: 80%
“…In the case of an as-deposited sample, the y-axis intercept is negative: the adjustment is not good (we have only three points available), the error covers the origin, so no conclusions can be obtained in this case. In a previous work with SrTiO 3based films (STO) we found different k-values for different film thicknesses as the crystallization intensities of these films were low for thinner films [19].…”
Section: Resultsmentioning
confidence: 80%
“…About two decades ago, deposition of conformal SrTiO 3 thin films by ALD at 325 °C was demonstrated using strontium bis­(cyclopentadienyl) [Sr­(Cp) 2 ] and titanium tetraisopropoxide as Sr and Ti precursors, respectively, and water as an oxidant. , After annealing in air at 500 °C, the deposited SrTiO 3 films were found to have measured permittivity values of around 180 . It has also been reported that the choice of precursors and oxidizers plays an important role in determining the quality of deposited thin films. , For instance, SrTiO 3 thin films deposited with [Sr­(demamp)­(tmhd)] 2 , titanium tetraisopropoxide, and O 3 exhibit dielectric constants of around 140 and acceptable leakage current densities . In many cases, reaction mechanisms underlying the ALD of perovskite oxides are still poorly understood, despite their importance.…”
Section: Introductionmentioning
confidence: 99%
“…12 It has also been reported that the choice of precursors and oxidizers plays an important role in determining the quality of deposited thin films. 25,26 For instance, SrTiO 3 thin films deposited with [Sr(demamp)-(tmhd)] 2 , titanium tetraisopropoxide, and O 3 exhibit dielectric constants of around 140 and acceptable leakage current densities. 9 In many cases, reaction mechanisms underlying the ALD of perovskite oxides are still poorly understood, despite their importance.…”
Section: Introductionmentioning
confidence: 99%